2017
DOI: 10.1073/pnas.1619932114
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically disordered chromatin protein NUPR1 binds to the C-terminal region of Polycomb RING1B

Abstract: Intrinsically disordered proteins (IDPs) are ubiquitous in eukaryotes, and they are often associated with diseases in humans. The protein NUPR1 is a multifunctional IDP involved in chromatin remodeling and in the development and progression of pancreatic cancer; however, the details of such functions are unknown. Polycomb proteins are involved in specific transcriptional cascades and gene silencing. One of the proteins of the Polycomb complex is the Ring finger protein 1 (RING1). RING1 is related to aggressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 73 publications
(107 reference statements)
3
72
0
Order By: Relevance
“…Fragments of the simulated protein structure with a length of 5 or 7 amino acid residues were used as receptors for molecular docking of either TFP or TFP-derived compounds, by using the AutoDock Vina software (45). The choice of using short fragments of NUPR1 was motivated not only by the necessity of reducing its exceedingly large conformational space, but also by the fact that ligand binding to the protein is dictated by local hydrophobicity spanning up to 7 amino acid residues (27,29). We previously proved that molecular docking is sufficiently accurate to reveal the binding locations of drugs to NUPR1 in a blind search (29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragments of the simulated protein structure with a length of 5 or 7 amino acid residues were used as receptors for molecular docking of either TFP or TFP-derived compounds, by using the AutoDock Vina software (45). The choice of using short fragments of NUPR1 was motivated not only by the necessity of reducing its exceedingly large conformational space, but also by the fact that ligand binding to the protein is dictated by local hydrophobicity spanning up to 7 amino acid residues (27,29). We previously proved that molecular docking is sufficiently accurate to reveal the binding locations of drugs to NUPR1 in a blind search (29).…”
Section: Methodsmentioning
confidence: 99%
“…Structurally, NUPR1 is an intrinsically disordered protein (IDP) with an entirely disordered conformation (5,(25)(26)(27)(28). Consequently, the target-based high throughput screening for drug selection toward this protein is highly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…It plays key roles in pancreatic tumorigenesis, acting downstream of the Kras G12D oncogene mutation, which is critical for pancreatic carcinogenesis (19). Furthermore, NUPR1 is involved in apoptosis by forming a complex with prothymosin  (20), another IDP, as well as implicated in DNA binding (21) and repair (22), through interaction with the male specific lethal protein (MSL1), and in the association to proteins of the Polycomb group (23). All these interactions provide the rationale to consider NUPR1 inhibition as a clinically feasible strategy to expand the PDAC drug arsenal.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that binding to all those biomolecules occurs through two distant regions of the NUPR1 sequence (20,(22)(23)(24): (i) the hydrophobic patch around Ala33, containing the two aromatic rings of the protein, Tyr30 and Tyr36; and, (ii) the region around Thr68, which is a polypeptide patch with relatively high hydrophobicity. The Ala33Gln and Thr68Gln mutants have both shown impaired binding to NUPR1 protein partners, therefore pinpointing the importance of those regions (23). As tested in PDAC-derived cell-based assays (24), both regions also intervene in the binding of small molecules capable of inducing cell-growth arrest and senescence, reduced cell migration, and decreased chemoresistance, thus mimicking NUPR1-deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A cell-based assay would also be required to test hits from the screen under in vivo conditions, for example proteins labeled with FRET donors and acceptors, co-immunoprecipitation or indirectly by measuring amounts of HIF1α. Although challenging due to several highly disordered regions in the HIF-1 protein, such screening would be still feasible as recently reported for inhibiting PPI in the cancer-associated and intrinsically disordered protein NUPR1 [148,149].…”
Section: Targeting the Chaperone Role Of Nqo1 To Inactivate Hif-1: Fmentioning
confidence: 99%